Problematic Internet use (PIU) in youth: A brief literature review of selected topics - Ruckwongpatr Kamolthip; Paratthakonkun Chirawat; Simin Ghavifekr; Wan Ying Gan; Serene Tung En Hui; Ira Nurmala; Siti R Nadhiroh; Iqbal Pramukti; Chung-Ying Lin (Elsevier Ltd, 2022)
We aimed to discuss several selected topics related to problematic Internet use (PIU), including fear of missing out, nomophobia, cyberchondria, cyberbullying, and certain health conditions (e.g. autism-spectrum disorder and schizophrenia) among youth. We also aimed to review some recent evidence examining PIU during COVID-19. The review was conducted using keywords relevant to the selected topics and searching in the PubMed database and Google Scholar. The results of this review indicate that PIU could be associated with health issues in a minority of the youth population. Moreover, the COVID-19 pandemic may lead to PIU and subsequent health problems. Information from this review could help healthcare providers to design individualized and appropriate interventions to tackle health issues related to PIU among youth.